expand and simplify:
multiply the 2 and 3 through their respected brackets
2x - 2 + 3 = x - 3x - 3
collect like terms, x terms on the left
2x + 3x - x = -3 + 2 - 3
simplify
4x = -4
x = -4/4 = -1
2007-01-20 06:27:37
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
2(x-1) + 3 = x - 3( x+1)
2 x -2 +3 = x - 3 x -3
2 x -x +3 x = -3 +2 -3
x+3 x = -6 +2
4 x = -4
x = - 4 /4
x= -1 reapply: 2( -1-1)+3 =-1 -3(-1+1)
-4 +3 = -1 - 0 ,,,,-1=-1
2007-01-20 06:37:01
·
answer #2
·
answered by Tuncay U 6
·
0⤊
0⤋
I'm assuming your solving for the x-variable, correct?
2(x - 1) + 3 = x - 3(x + 1)
First: eliminate the parenthesis > multiply the outer (terms in front of the parenthesis) terms with the terms in the parenthesis...
2(x) - 2(1) + 3 = x - 3(x) - 3(1)
2x - 2 + 3 = x - 3x - 3
*Combine "like" terms...
2x + 1 = -2x - 3
Sec: subtract "1" from both sides...
2x + 1 - 1 = -2x - 3 - 1
2x = - 2x - 4
*Add "2x" to both sides...
2x + 2x = - 2x + 2x - 4
4x = - 4
Third: solve for "x" by isolating it on one side > divide both sides by 4...
4x/4 = - 4/4
x = - 1
2007-01-20 06:29:25
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
2(x-1)+3=x-3(x+1)
2x - 2 + 3 = x - 3x - 3
2x + 1 = -2x - 3
4x = -4
x = -1.
Ck.
2(-2) + 3 = -4 + 3 = -1.
and
(-1) - 3(0) = -1.
2007-01-20 06:30:54
·
answer #4
·
answered by S. B. 6
·
0⤊
0⤋
2x - 2 + 3 = x - 3x -3
2x + 1 = -2x -3
2x + 2x = -3 -1
4x = -4
x = -1
Solution: {x elements of R | x = -1}
::
2007-01-20 07:40:58
·
answer #5
·
answered by aeiou 7
·
0⤊
0⤋
2x-2+3=x-3x-3
2x+1=-2x-3
2x+2x = -3-1
4x = -4
so x = -4/4
so x = -1
2007-01-20 06:27:41
·
answer #6
·
answered by Jordi 2
·
0⤊
0⤋